CONCEPTUAL-CATEGORICAL APPARATUS OF SOCIAL WORK IN THE FIELD OF JUVENILE DELINQUENCY AS A REFLECTION OF THEORETICAL APPROACHES - Petrović, Jagoda P (Politeia, 2019)
Starting from the fact that theories of social work form a specific language, the subject of research is the conceptual-categorical apparatus of social work in the field of juvenile delinquency, as an indicator of theoretical foundations in the practice of social work. The basic research question is whether the conceptual-categorical apparatus of the profession of social work reflects traditional theoretical conceptions (positivist and structural-functional) or contemporary (existentialism, interactionist-constructivist, and radical-critical). By means of analysing the contents of 100 official documents collected from five centres for social work in the Republic of Srpska, we identify the key terms, the frequency of using these terms, and the context in which they are used. The results of the research show that the conceptual-categorical apparatus of the profession of social work reflects the positivist-structural-functionalist theoretical conceptions. The traditional approaches in social work, those of correctional-protective social work and the medical model of social work discourage any sort of active participation of social workers. The development of science of social work, the promotion of social work education, and new professional staff should advance the profession in accordance with the basic postulate of modern social work - the production of social changes.